Effects of low-protein, amino acid- fortified diets, formulated on a net energy basis, on the growth performance and carcass characteristics of finishing pigs - Smith, J.W.II; O'Quinn, P.R.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred eighty-eight gilts were used to determine the effects of corn-soybean meal or low-protein, amino acid-fortified diets, formulated on a net energy (NE) basis on growth perforn1ance and carcass characteristics. Pigs fed high NE grew faster from 105 to 165 lb. However, pigs fed diets with intact protein grew faster and more efficiently during the finishing period and for the entire trial than those fed low protein, amino acidfortified diets. Carcass data revealed that pigs consuming high NE were fatter and had lower percentage lean than pigs consuming low NE. Additionally, longissimus muscle area tended to be greater in pigs fed diets containing intact protein than pigs fed low protein, amino acid-supplemented diets. Based on these results, pigs fed low protein, amino acid-fortified diets had poorer ADG, feed efficiency, and carcass leanness than those fed diets with intact protein, regardless of NE.
Keywords: Swine; Growing-finishing pigs; Net energy